Clean Water Pipeline Network Optimization using Minimum Spanning Tree Algorithms in Argopuro Housing, Jember - Agustina Pradjaningsih; Audy Putri Lestari; Firda Fadri; Apriani Soepardi (ZERO: Jurnal Sains, Matematika dan Terapan, 2026)
Infrastructure development requires cost-efficient planning to ensure sustainable urban services. This study optimized the clean water pipeline network in Argopuro Housing, Jember, using Minimum Spanning Tree algorithms. The system was modeled as a weighted undirected graph representing junctions and pipe segments. Four algorithms Prim’s, Kruskal’s, Sollin’s, and Borůvka’s were applied to determine the optimal configuration and evaluate computational performance. All algorithms produced the same optimal pipeline length of approximately 31.00 km, representing a 40.24% reduction from the initial network. Execution time differed, with Prim’s algorithm being the fastest (0.0008 s), followed by Kruskal’s (0.0012 s), Borůvka’s (0.0067 s), and Sollin’s (0.2476 s). These results demonstrate that MST-based optimization effectively improves network efficiency. However, the study was limited to a single dataset and pipeline length as the main criterion. Future research should incorporate additional constraints and larger network scenarios for broader applicability.